Recent Progress in the Gold-Catalyzed Annulations of Ynamides with Isoxazole Derivatives via α-Imino Gold Carbenes - Li, Long; Luo, Wen-Feng; Ye, Long-Wu (Synlett, 2021)
During the past two decades, gold-catalyzed nitrene-transfer reactions via α-imino gold carbenes have received extensive attention, as this strategy provides rapid access to nitrogen-containing molecules with high efficiency. In this review, we focus on recent progress in gold-catalyzed formal annulations of ynamides with isoxazole derivatives as nitrene-transfer reagents via α-imino gold carbenes in atom-economic and rapid construction of N-heterocycles.
Keywords: gold catalysis; gold carbenes; ynamides; isoxazoles; annulations; N-heterocycles